(untitled) (Revista de Ciências Agroveterinárias, 2018)
The studies of the fragility of the environments are significant and important for the environmental and territorial planning, since it is a tool that analyzes and identifies environments in relation to their different levels of vulnerability. The letter of fragility assists in a diagnosis where the problems can be corrected and intervene in future actions. The present work was elaborated with the objective of determining the environmental fragility of a hydrographic basin of the city of Presidente Prudente, SP, that had not been previously studied. This methodology aims to identify areas that present greater or lesser fragilities, resulting from anthropic pressures arising from different types of land use and occupation. Through this study, it observed that this basin presents a predominance of medium potential fragility, followed by strong potential fragility. This result indicates a large predominance of herbaceous vegetation, shallow soils and areas unsuitable for the implantation of anthropic activities due to the high slope.